2010
DOI: 10.1007/s10658-010-9697-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative studies on downy mildew (Peronospora destructor Berk. Casp.) affecting onion seed production in southern Uruguay

Abstract: Onion downy mildew (Dm) symptoms and damage on seed production fields in southern Uruguay were quantified during two seasons as the progress of incidence, severity, and as the effect of the level of seed-stalks infections on seed yield and quality. In addition, the effects of two plantation dates and two plant densities on Dm were studied in a factorial experiment. Maximum incidence along the season ranged from 15 to 65% in four commercial fields in 2005 and two fields in 2006. Maximum severity ranged from 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the disease survey fields, symptoms of downy mildew caused by secondary infections appeared earlier in early maturing onion varieties than in the medium-latematuring onion varieties in 2016, 2017, and 2018 (Figures 5-7). Several studies have reported that host-plant age and size can affect the incidence of onion downy mildew, as shown below; thus, even in favourable environments for disease development, it has been observed that onset occurred at 9 weeks after transplanting [39] or that disease development only occurred late in the growing season [40]. Furthermore, in a study examining the effects of planting date on onion plants, the size of plants when the first symptoms of downy mildew were observed was approximately 25 cm in length [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the disease survey fields, symptoms of downy mildew caused by secondary infections appeared earlier in early maturing onion varieties than in the medium-latematuring onion varieties in 2016, 2017, and 2018 (Figures 5-7). Several studies have reported that host-plant age and size can affect the incidence of onion downy mildew, as shown below; thus, even in favourable environments for disease development, it has been observed that onset occurred at 9 weeks after transplanting [39] or that disease development only occurred late in the growing season [40]. Furthermore, in a study examining the effects of planting date on onion plants, the size of plants when the first symptoms of downy mildew were observed was approximately 25 cm in length [41].…”
Section: Discussionmentioning
confidence: 99%
“…The seed certification program created opportunities for research in seed production technology, encompassing various aspects of crop protection and management (Gonzaĺez et al, 2011;Peluffo et al, 2016b). Thanks to the genetic richness of onion landraces, improved cultivars enabled their competitiveness in major vegetable markets.…”
Section: Onion Landraces In Uruguaymentioning
confidence: 99%